Delayed Repositioning in Teeth with Horizontal Root Fracture: Two Case Reports - Mahshid Sheikhnezami; Nima Mokhber; Khosro Shamsian; Salman Saket; Hamid Jafarzadeh (Mashhad University of Medical Sciences, 2017)
Introduction: Horizontal root fracture (HRF) generally has a good prognosis of healing at fracture line after repositioning and flexible splinting. However, various factors such as delayed referral may unfavorably influence close reduction of firmly displaced coronal fragments and the long-term prognosis of healing at fracture line. Case 1: A 25-year-old woman with HRF in her maxillary central incisors was referred 1 week after trauma. Repositioning of the displaced coronal fragment was not successful for the left central incisor. Despite questionable prognosis for this case, reduction and flexible splinting was performed after removing it's coronal fragment, minor curettage in alveolar socket and immediate replanting. Calcium hydroxide dressing and MTA plug placement for the coronal fragment were carried out after 1 and 3 weeks, respectively. The crown was restored and a minor permanent splint was applied after splint removal. Case 2: The above protocol was applied for a 17-year-old boy with HRF in his left maxillary central incisor. He referred 3 weeks after trauma with a firmed displaced coronal fragment. At four-year follow-up in both patients, the teeth were clinically in function and the patients were asymptomatic. The periapical radiographs revealed complete healing at fracture lines.